Hong Kong's link to the US dollar : origins and evolution - Greenwood, John (Hong Kong University Press ; Eurospan [distributor], 2008)
This book covers the origins of Hong Kong's currency crisis in 1983, the initial resolution of the crisis by creation of a currency board, the subsequent problems leading to the Asian financial crisis of 1997-98, and the later reforms. The Epilogue traces Hong Kong's monetary developments between 1990 and 2005.